2020
DOI: 10.3390/coatings10121208
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Deposition of Lead Iodide and Lead Chloride Thin Films by Low-Pressure Chemical Vapor Deposition

Abstract: Lead halide thin films, such as lead iodide (PbI2) and lead chloride (PbCl2), are used as precursor films for perovskite preparation, which is frequently achieved by vacuum thermal evaporation but rarely by the low-pressure chemical vapor deposition (CVD) method. Here, we report on the deposition of PbI2 and PbCl2 thin films on glass substrates by employing the low-pressure CVD method. The effect of the substrate temperature on the structure and morphology of the lead halide films is investigated. Crystalline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Peaks related to Pb can be distinguished in the patterns recorded for the originally obtained compound as well as for the product formed during its thermal modification at 600 °C. 41,42 It means that chemical modification in H 2 O 2 as well as heat treatment at 800 °C result in almost complete removal of lead from the investigated compounds. Contrary to the EDS surface analysis, XRD measurements revealed the presence of Pb within the originally obtained compound.…”
Section: Resultsmentioning
confidence: 99%
“…Peaks related to Pb can be distinguished in the patterns recorded for the originally obtained compound as well as for the product formed during its thermal modification at 600 °C. 41,42 It means that chemical modification in H 2 O 2 as well as heat treatment at 800 °C result in almost complete removal of lead from the investigated compounds. Contrary to the EDS surface analysis, XRD measurements revealed the presence of Pb within the originally obtained compound.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the narrow temperature distribution, we found that the vertical substrate exhibited position-dependent thickness variations, albeit to a lesser extent than the horizontal substrate (Figure d). Observations from the vertical substrate, including low surface roughness (Figure a), low average film thickness (Figure c), and high surface coverage (Figure e), suggest that layer-by-layer growth is favored under conditions of significant mass transport limitation. , The crystal structure of PbI 2 is similar to that of two-dimensional (2D) transition metal dichalcogenides (TMDs), characterized by layered structures with weak vdW interactions. , Consequently, film formation adheres to Frank-van der Merwe (FM) type growth modes, involving the coalescence of 2D flakes through the surface diffusion of PbI 2 molecules transported from the bulk flow. This mass transport is contingent on boundary layer development, which is, in turn, influenced by the flow geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Thermally evaporated PbI 2 has previously been used for applications, including X-ray detection, photoemission, and photovoltaics; , however, thermal evaporation requires temperatures approaching 400 °C to vaporize the PbI 2 powder and lacks the atomic-level thickness control that is enabled by ALD processes. CVD of PbI 2 encounters similar limitations, requiring higher substrate temperatures than ALD and typically resulting in thicker films with poor control over thickness. , …”
Section: Introductionmentioning
confidence: 99%